(untitled) (Plant Tissue Culture and Biotechnology, 2025)
An efficient in vitro regeneration protocol for a rare medicinal plant, Cynanchum callialatum Buch.-Ham. ex Wight was established. Explants for this study were obtained from aseptically grown healthy green seedlings on MS medium. The shoot apices, nodal and leaf segments from in vitro grown seedlings were cultured on MS medium containing different concentrations and combinations of PGRs. The shoot apices and nodal segments underwent direct organogenesis. The highest number of shoot apices (95%) produced multiple shoot buds (5.31 ± 0.14 per explant) when cultured on MS + 2.0 mg/l BAP + 1.0 mg/l NAA. On the other hand, 87% of nodal segments responded to induction of multiple shoot buds (5.26 ± 0.14 per nodal segment) when cultured on MS + 2.0 mg/l BAP + 1.5 mg/l NAA. The highest number of leaf segments (100%) produced whitish friable calli on MS + 1.0 mg/l 2,4-D + 1.0 mg/l BAP. It was noticed that this whitish friable callus did not undergo any kind of differentiation. The elongated shoot buds were individually grown on rooting media. The maximum number of roots (6.82 ± 0.10) per shoot was produced in half-strength MS medium fortified with 2.0 mg/l IBA. After successive phases of acclimatization, 75% of the plantlets were finally survived and established showing normal growth. Plant Tissue Cult. & Biotech. 35(1): 199-207, 2025 (June)